Community attitude and perception on conserving the water quality in Inanam-Likas River Basin (ILRB), Kota Kinabalu, Sabah / Florrissa Florist Mosiun - Mosiun, Florrissa Florist (Faculty of Applied Sciences, 2017)
The rapid developments nowadays cause the conservation of water quality to being neglected. In addition, the community attitude and perception towards water quality conservation will influence the water quality status in one particular area. This study intends to identify the current water quality status, investigate the community attitude and perception regarding water quality conservation and the correlation between those two in Inanam-Likas River Basin (ILRB). The study was conducted by carrying out the water quality testing of both in-situ and ex-situ methods and the correlation by using IBM SPSS Statistics 23. To identify the water quality, several physical and chemical parameters were used such as temperature, pH, Dissolved Oxygen (DO), nitrate (NO3-) and phosphorus (PO43-). According to the conducted analysis, Station 2 has the highest index and Station 3 has the lowest index of water quality. The highest index among the four stations classified as good while the lowest index classified as medium water quality status. The community attitude and perception data were gathered by using questionnaire among the respondents prior running the correlation analysis. Overall, the study suggests that there is an association between the current water quality and community attitude and perception on conserving the water quality in Inanam-Likas River Basin (ILRB) even though the correlation is not strong which is lie on +0.199. Thus, the water quality must be maintained and conserved for a long time for the benefits of all related parties especially those who are living in that particular area.